The The Influence of English Song to IMPROVELISTENING SKILL (INTEGRATION PROCEEDING, 2023)
This is a conceptional article which the writer proposes a concept of the influence of English song to improve listening skill. In English language teaching, there are various kinds of available media that can be used to improve listening skill. Hypothetically, one of the best media to learn listening skill is by using song. Because by listening the songs, the students can learn listening skill anywhere and anytime in an easy and fun way. In fact, English song are the easiest and simplest media for learning English which most students are often used. They will learn listening skill by listening to the songs many times. Thus, memories are also formed through repetition. In short, using songs will be an effective media for students to master listening skill.